2007
DOI: 10.1111/j.1528-1167.2006.00974.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Pattern of Epilepsy Treatment in Different Socioeconomic Classes in Brazil

Abstract: Summary: Purpose:The worldwide prevalence of epilepsy is variable, estimated at 10//1,000 people, and access to treatment is also variable. Many people go untreated, particularly in resourcepoor countries.Objective: To estimate the prevalence of epilepsy and the proportion of people not receiving adequate treatment in different socioeconomic classes in Brazil, a resource-poor country.Methods: A door-to-door survey was conducted to assess the prevalence and treatment gap of epilepsy in three areas of two towns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
1
31

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(97 citation statements)
references
References 20 publications
4
61
1
31
Order By: Relevance
“…The differences are in part related to different study designs and differences regarding the defi nitions of active epilepsy. Some stud-ies require two or more unprovoked seizures in the year before the index date to be considered "active epilepsy" [4][5]8••]; others use a 2-year period [9] or 5-year period [10•,11-15,16•,17•]. Limiting assessment to studies that provide information for age-adjusted rates (Table 1), the average age-adjusted prevalence of active epilepsy is 8.5 per 1000 people.…”
Section: Prevalence and Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…The differences are in part related to different study designs and differences regarding the defi nitions of active epilepsy. Some stud-ies require two or more unprovoked seizures in the year before the index date to be considered "active epilepsy" [4][5]8••]; others use a 2-year period [9] or 5-year period [10•,11-15,16•,17•]. Limiting assessment to studies that provide information for age-adjusted rates (Table 1), the average age-adjusted prevalence of active epilepsy is 8.5 per 1000 people.…”
Section: Prevalence and Incidencementioning
confidence: 99%
“…Demonstration projects have been carried in China [4], Togo [56], Brazil [9], Senegal [6], and Vietnam [17•].…”
Section: Carementioning
confidence: 99%
“…An epidemiological study in São Paulo State found a lifetime prevalence of epilepsy of 9.2/1,000 [95% CI 8.4-10.0] 5 . Stigma is present in our s o c i e t y, excluding people with epilepsy from social activities, particularly because of misinformation but also due to lack of appropriate attitudes held by health professionals 3 .…”
mentioning
confidence: 99%
“…Based on our epidemiological surv e y 5 it is estimated that about one million people in Brazil have active epilepsy, of whom approximately 40% do not receive adequate t re a t m e n t 5 . Consequently, epilepsy is considered a public health problem, especially in re s o u rc e -p o o r countries.…”
mentioning
confidence: 99%